2004
DOI: 10.1212/01.wnl.0000113759.80877.1f
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neuropsychological test performance in asymptomatic carotid stenosis

Abstract: Carotid stenosis was associated with poorer neuropsychological performance. This could not be explained by a higher proportion of silent MRI lesions in persons with asymptomatic carotid stenosis, making it less likely that the cognitive impairment was caused by silent emboli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
165
2
12

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(192 citation statements)
references
References 27 publications
13
165
2
12
Order By: Relevance
“…However, recent articles have demonstrated that even asymptomatic patients with an elevated ICA luminal narrowing show higher depression scores or reduced neuropsychologic test performances that seem to be reversed by CAS. [24][25][26] It is, therefore, tempting, in view of these works on the neuropsychological effect of carotid stenosis, to hypothesize that the low-normal perfusion observed in our patient population, reversed by the stent-placement procedure, could be the cause of serious long-term effects consisting of either clinically evident depression, severely reduced attention, or mem Fig 1. A, An example of ICA flow territory (red) in a population with a nonvariant type of circle of Willis. B and C, CBF (mL/100 g per minute) and MTT (seconds) ory impairment, ultimately perhaps contributing to the development of dementia.…”
Section: Discussionmentioning
confidence: 88%
“…However, recent articles have demonstrated that even asymptomatic patients with an elevated ICA luminal narrowing show higher depression scores or reduced neuropsychologic test performances that seem to be reversed by CAS. [24][25][26] It is, therefore, tempting, in view of these works on the neuropsychological effect of carotid stenosis, to hypothesize that the low-normal perfusion observed in our patient population, reversed by the stent-placement procedure, could be the cause of serious long-term effects consisting of either clinically evident depression, severely reduced attention, or mem Fig 1. A, An example of ICA flow territory (red) in a population with a nonvariant type of circle of Willis. B and C, CBF (mL/100 g per minute) and MTT (seconds) ory impairment, ultimately perhaps contributing to the development of dementia.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, patients showed distinct decreases in neuropsychologic test scores, particularly with regard to verbal fluency and memory, as well as cognitive flexibility and executive functions, in line with previous studies of our group and others. 11,27 Changes in memory performance may have been mediated by the diminished connectivity within the DMN regions found in the patients group; in fact, decreased connectivity in the DMN has previously been associated with lower scores on tasks of executive function and processing speed in cognitively normal older adults, 28 as well as with lower memory functions in patients with mild cognitive impairment when compared with HC. 29 In the current study, decreases in interhemispheric functional connectivity in the default mode (pIPL) and the frontoparietal (DLPFC) networks were correlated with lower scores on verbal fluency and delayed recall, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…[15][16][17][18][19][20][21][22] An association between IMT and cognitive impairment has been reported, 2,12,23 and has been shown to extend to stroke free persons. 24 The objective of this study is examine whether socioeconomic status (SES) moderates, or is an effect modifier of, the association between IMT and cognition. Socioeconomic advantage has been shown to buffer adverse effects of certain exposures, low birth weight is a much explored example.…”
Section: Introductionmentioning
confidence: 99%